2017
DOI: 10.1038/srep43316
|View full text |Cite
|
Sign up to set email alerts
|

Insula and somatosensory cortical myelination and iron markers underlie individual differences in empathy

Abstract: Empathy is a key component of our ability to engage and interact with others. In recent years, the neural mechanisms underlying affective and cognitive empathy have garnered intense interest. This work demonstrates that empathy for others depends upon a distributed network of regions such as the insula, parietal cortex, and somatosensory areas, which are also activated when we ourselves experience an empathized-with emotion (e.g., pain). Individuals vary markedly in their ability to empathize with others, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 94 publications
2
17
0
Order By: Relevance
“…Emma Duerden et al used quantitative meta-analytic methods and found that perceiving emotions in others activated bilateral anterior insula (Duerden, Arsalidou, Lee, & Taylor, 2013). Many other studies also highlighted that the AI was a component of the core networks involved in empathy (Allen et al, 2017;Bernhardt & Singer, 2012;Chakrabarti, Bullmore, & Baron-Cohen, 2006;Jabbi, Swart, & Keysers, 2007;Lamm et al, 2011;Singer et al, 2004). Lesion study provided further evidence that the insula damage may lead to decreased affective response to and decreased withdrawal from painful stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Emma Duerden et al used quantitative meta-analytic methods and found that perceiving emotions in others activated bilateral anterior insula (Duerden, Arsalidou, Lee, & Taylor, 2013). Many other studies also highlighted that the AI was a component of the core networks involved in empathy (Allen et al, 2017;Bernhardt & Singer, 2012;Chakrabarti, Bullmore, & Baron-Cohen, 2006;Jabbi, Swart, & Keysers, 2007;Lamm et al, 2011;Singer et al, 2004). Lesion study provided further evidence that the insula damage may lead to decreased affective response to and decreased withdrawal from painful stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Our results extend this work and suggest that the neural circuits that have been implicated in feelings have functional connectivity with the DMN and that a disorder such as psychotic depression impacts this functional connectivity. Another possibility relates to a recent quantitative MRI study that suggests insular and somatosensory cortices are responsible for processing trait behaviours associated with empathy [ 34 ]. Our study does not permit the exploration of whether the observed functional connectivity patterns specifically relate to processing feelings or empathy.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining participants ( n = 59; mean age ± SD: 23.9 ± 4.9; 32 female, 27 male) were sampled from the general population through local participant pools. These subjects took part in three experiments: one exploring the potential association between auditory perceptual abilities, musicianship, tonotopic organization and structural properties of the auditory cortex (data not reported here), one investigating the relationship of trait empathy and brain microstructure ( Allen, Frank, et al., 2017 ), and a third investigating metacognition and MPM assays ( Allen et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%